2012
DOI: 10.1111/j.1875-595x.2011.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Does smoking increase the incidence of postoperative complications in simple exodontia?

Abstract: Objective:  To investigate whether smoking has adverse effects in simple exodontia. Methods:  A single‐centre, prospective study of postoperative inflammatory complications in simple exodontia was performed. All procedures were conducted under similar and sterile conditions. Postoperative complications (PCs) in exodontia were classified as alveolar osteitis (AO) or alveolar infection (AI) and their incidences then added. Results:  A logistic regression model for PCs revealed tooth sectioning [odds ratio (OR) =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…Moreover, several studies demonstrated the correlation between dry socket and smoking habit [21,22]; cigarette smoking reduces the post-operative socket filling with blood, so wound healing is slowed down [23]. Furthermore, the presence of nicotine, which is a cytotoxic substance [24], interferes with the expression of a number of genes which play an essential role in the formation of new vessels and in bone healing, leading to an increased catabolic response that may be unfavorable to new bone formation, negatively affecting wound healing [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies demonstrated the correlation between dry socket and smoking habit [21,22]; cigarette smoking reduces the post-operative socket filling with blood, so wound healing is slowed down [23]. Furthermore, the presence of nicotine, which is a cytotoxic substance [24], interferes with the expression of a number of genes which play an essential role in the formation of new vessels and in bone healing, leading to an increased catabolic response that may be unfavorable to new bone formation, negatively affecting wound healing [25].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high rate of this complication after third molar extractions and surgeries, prevention of this complication has been the focus of number of publications in this field. Based on the published papers, various risk factors have been outlined in development of AO including age, gender, menstrual cycle and oral contraceptives in women, periapical infection in the area, difficulty of the surgery and amount of trauma during the surgery, impaction pattern of the third molar, surgeon's experience, amount of socket irrigation during the surgery, and number of anesthetic cartridges used to anesthetize the patient [5][6][7][8][9][10]. One of the main challenges in this field is to prevent AO after third molar surgery.…”
Section: Introduction and Discussionmentioning
confidence: 99%
“…Once the patients came for routine follow-ups, the site of surgery was examined for healing or presenting complications such as trismus, dry socket, lingual nerve damage, inferior alveolar nerve damage, and infection. Trismus was defined as mouth opening less than 10 mm measured in correlation to the incisal edges of the upper and lower incisal edges, [7] dry socket was examined for signs and symptoms such as severe pain which could not be controlled with analgesics post 3 days of surgery and empty foul smelling socket with loss of primary sutures. [8] Nerve damage was examined as any neurosensory change observed subjectively in the patient through touch or prick performed by the investigators.…”
Section: Variablesmentioning
confidence: 99%